Development of Bontang’s White Bread with the Use of Mackerel Tuna (Euthynnus affinis) Broth - Zulfiqo Ilham Chudori; Nunung Nurjanah (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2024)
The development of white bread food products using mackerel tuna fish broth is a variation of innovation to produce a good nutritional value of animal protein. This research method uses experimental research methods. This research was conducted using a completely randomized design (CRD) to see differences in texture, aroma, taste, water content, and development of white bread added to mackerel tuna fish broth by 36%, 42%, and 48%. Each treatment has two repetitions, followed by physical tests (white bread development volume), hedonic tests (texture, taste, and aroma), and chemical tests (water content). The data obtained were analyzed statically using the ANOVA test, then continued with the DMRT (Duncan's Multiple Range Test) test if there were differences. The research results showed significant differences in the organoleptic hedonic properties and chemical and physical tests of white bread development.